2018
DOI: 10.1159/000485796
|View full text |Cite
|
Sign up to set email alerts
|

Four-Week Strategy-Based Training to Enhance Prospective Memory in Older Adults: Targeting Intention Retention Is More Beneficial than Targeting Intention Formation

Abstract: Background: So far, training of prospective memory (PM) focused on very short instances (single sessions) and targeted the intention-formation phase only. Objective: We aimed to compare the effectiveness of 2 different 4-week strategy-based PM training types, namely imagery training (targeting the encoding of the PM intention in the intention-formation phase) versus rehearsal training (targeting the maintenance of the PM intention in the intention-retention phase) in older adults. Methods: We used a 4-week tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
(51 reference statements)
0
6
1
Order By: Relevance
“…It was revealed that plan retention could predict intention initiation and plan fidelity. A study showed that rehearsal training that targeted intention maintenance outperformed imagery training that targeted intention encoding and formation for older adults [38]. However, the present study showed that mental imagery may work on not only intention formation but also intention retention, thereby facilitating performance in subsequent PM phases.…”
Section: Discussioncontrasting
confidence: 63%
“…It was revealed that plan retention could predict intention initiation and plan fidelity. A study showed that rehearsal training that targeted intention maintenance outperformed imagery training that targeted intention encoding and formation for older adults [38]. However, the present study showed that mental imagery may work on not only intention formation but also intention retention, thereby facilitating performance in subsequent PM phases.…”
Section: Discussioncontrasting
confidence: 63%
“…In this context, research suggests that learning to frequently and actively monitor for PM cues can improve performance (Umanath, Toglia, & McDaniel, 2016). Similarly, in recent study, Ihle, Albinski, Gurynowicz, and Kliegel (2018) show that repeatedly rehearsing the planned actions (thinking of which tasks one was supposed to do) can increase PM performance of older adults. Thus, it may be beneficial to teach older adults to regularly think of what they had planned to do, to evaluate and control their activities and to strategically check the clock.…”
Section: Practical Implications and Outlook: How To Promote Prospecti...mentioning
confidence: 62%
“…Cognitive functioning (CF) declines with age. There is evidence that regular physical exercise (Bherer, Erickson, & Liu-Ambrose, 2013;Northey, Cherbuin, Pumpa, Smee, & Rattray, 2018) and cognitive training (Ballesteros, Kraft, Santana, & Tziraki, 2015;Ihle, Albiński, Gurynowicz, & Kliegel, 2018) are non-pharmaceutical interventions that attenuate age-related cognitive decline, and improve CF in older people.…”
Section: Background and Objectivesmentioning
confidence: 99%